Hydrothermal dynamics in a CM‐based model of Ceres. (28th June 2018) - Travis, B. J.; Bland, P. A.; Feldman, W. C.; Sykes, M. V.
Abstract: A 2‐D numerical study of the evolution of Ceres from a "frozen mudball" to the present era emphasizes the importance of hydrothermal processes. Particulates released as the "frozen mudball" thaws settle to form a roughly 290 km radius core. Hydrothermal flow is driven by radiogenic heating and serpentinization. Both salt‐free and brine fluids are considered. Our modeling suggests that Ceres's core has been warm over most of its history and is still above freezing, and convective processes are active in core and mantle to the present. The addition of low eutectic solutes greatly expands the region of active convection. A global muddy ocean persists for the first 3 Gyr, and at present, there may be several regional mud seas buried under a frozen crust. Transport of interior material to the near surface occurs throughout our model's history. Eutectic brines drive convective flow to near the surface, even breaching the surface in isolated regions, on the order of 30 km in width, similar in size to some mounds detected using the Dawn visible imaging camera (Sizemore et al. 2015). Surface features such as the bright spot in Occator crater and Ahuna Mons could be the result of eutectic plumes. The CM‐based model density profile is within 10% of Ermakov et al.'s (2017 ) results. The model mud mantle has a roughly 42:58 volumetric partitioning of H2 O to rock. Our mud model is consistent with the absence of large craters (Marchi et al.2016 ) and an internal viscosity decreasing with depth (Fu et al.2017 ).